Home » Past Questions » Mathematics » Simplify 3\(\frac{1}{3}\) - 1\(\frac{1}{4}\) x \(\frac{2}{3}\) + 1\(\frac{2}{5}\)...

Simplify 3\(\frac{1}{3}\) - 1\(\frac{1}{4}\) x \(\frac{2}{3}\) + 1\(\frac{2}{5}\)...


Question

Simplify 3\(\frac{1}{3}\) - 1\(\frac{1}{4}\) x \(\frac{2}{3}\) + 1\(\frac{2}{5}\)

Options

A) 2

B) 3

C) 4

D) 5

The correct answer is C.

Explanation:

3 - \(\frac{1}{3}\) - (\(\frac{5}{4}\) x \(\frac{2}{3}\)) + 1\(\frac{2}{5}\)
= \(\frac{10}{3}\) - \(\frac{5}{6}\) + \(\frac{7}{5}\)
= \(\frac{100 - 25 + 42}{30}\)
= \(\frac{117}{30}\)
= 3.9
\(\approx\) 4

More Past Questions:


Dicussion (1)

  • 3 - \(\frac{1}{3}\) - (\(\frac{5}{4}\) x \(\frac{2}{3}\)) + 1\(\frac{2}{5}\)
    = \(\frac{10}{3}\) - \(\frac{5}{6}\) + \(\frac{7}{5}\)
    = \(\frac{100 - 25 + 42}{30}\)
    = \(\frac{117}{30}\)
    = 3.9
    \(\approx\) 4

    Reply
    Like